Feasibility study on improving of 5-seater helicopter forward flight speed - Nik Mohd., Nik Ahmad Ridhwan (2006)
In this study, two 5-seater helicopters that are in the same FAR 27 category were chosen for the forward flight speed comparison. In order to improve the helicopter cruising speed, the main rotor blade of a helicopter that posses a lesser flight speed was modified through the usage of different number of main rotor blade (from 3 to 4 blades), different value of blade solidity and the usage of new engine with better performance. For design and analysis purposes, the appropriate theory i.e. the closed-form equation from blade element theory (BET) which deals with both the blade dynamics and aerodynamics was used. By considering the retreating blade stall, figure of merit and the growth of reverse flow area, the new combination of rotor and engine that is suitable for a better helicopter cruising speed performance were obtained. For data comparison, the results obtained from BET analysis then were compared with the results obtained from the computational fluid dynamic (CFD) based analysis. Using CFD approach, the FLUENT software was used and the multiple reference frames (MRF) method was used to simulate the helicopter main rotor at steady and level flight condition. Finally, the performance results of the current and the new rotor design obtained from the BET and CFD analysis then were compared with the other helicopter forward flight speed performance and found that they were in good agreement.